2009
DOI: 10.1016/j.chembiol.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A Small Molecule That Blocks Fat Synthesis By Inhibiting the Activation of SREBP

Abstract: Sterol regulatory element binding proteins (SREBPs) are transcription factors that activate transcription of the genes involved in cholesterol and fatty acid biosynthesis. In the present study, we show that a small synthetic molecule we previously discovered to block adipogenesis is an inhibitor of the SREBP activation. The diarylthiazole derivative, now called fatostatin, impairs the activation process of SREBPs, thereby decreasing the transcription of lipogenic genes in cells. Our analysis suggests that fato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
217
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(238 citation statements)
references
References 34 publications
15
217
0
Order By: Relevance
“…Mvd, a lipogenic enzyme, was downregulated in ob/ob mice receiving fatostatin treatment [53]. The expression of Pcsk9, associated with hypercholesterolemia, decreased after berberine treatment of HFD-induced obese mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…Mvd, a lipogenic enzyme, was downregulated in ob/ob mice receiving fatostatin treatment [53]. The expression of Pcsk9, associated with hypercholesterolemia, decreased after berberine treatment of HFD-induced obese mice [54].…”
Section: Discussionmentioning
confidence: 99%
“…3D) in 1-LN and DU-145 prostate cancer cells stimulated with ␣ 2 M*. Previous studies of head and neck tumors have shown a correlation of high lactate levels with an increased incidence of metastasis (91 (Fig. 4, C and D).…”
Section: Elevated Glucose Uptake In Prostate Cancermentioning
confidence: 99%
“…6). Pretreatment of prostate cancer cells with inhibitors of PI 3-kinase/Akt/mTORC or fatty-acid synthase significantly reduced ␣ 2 M*/insulin-induced increased phosphatidylcholine synthesis from 1-[ 14 (91,92). Stimulation of prostate cancer cells with ␣ 2 M*, similar to insulin, up-regulated protein synthesis 2-3-fold in 1-LN, DU-145, and LnCap cells compared with buffer-treated controls, although pretreatment of cells with fatostatin A nearly abolished these effects (Fig.…”
Section: ␣ 2 M* and Insulin Increase The Incorporation Of 1-[ 14 C]acmentioning
confidence: 99%
“…SREBP is an important transcription factor that activates cholesterol-synthesizing genes. Small molecule inhibitors of SREBP are highly desirable due to their potential to treat atherosclerosis (Kamisuki et al, 2009). ER-b selective agonists markedly (6-to 7-fold) decreased SREBP in white adipose tissue of animals fed with a high-fat diet compared with vehicletreated animals.…”
Section: Er-b Selective Ligands As Novel Therapeutics For Obesity Andmentioning
confidence: 99%